Quality of life among elderly individuals with hypertension in Indonesia - Rahmaningtia, Nabilla; Luthfa, Iskim; Aspihan, Mochammad (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Backgroud: Hypertension is a chronic disease that often affects older adults due to the aging process and can reduce physical, psychological, social, and environmental functioning, thereby impacting quality of life. Purpose: To determine the quality of life of elderly people with hypertension in the working area of the Bangetayu Community Health Centre in Semarang. Method: The study used a quantitative descriptive design with a cross-sectional approach involving 132 elderly people with hypertension who were selected using total sampling techniques. Data collection was conducted using the WHOQOL-BREF questionnaire, then analysed descriptively to describe the quality of life in the physical, psychological, social, and environmental domains. Results: The results showed that most elderly people with hypertension had a relatively good quality of life in all domains measured, although physical limitations due to the aging process were still found. Conclusion: This study shows that the quality of life of elderly people with hypertension in the Bangetayu Community Health Centre working area is relatively good and needs to be maintained through physical health maintenance efforts, psychosocial support, and empowerment of the elderly in social activities. Keywords: Ederly; Hypertension; Quality of Life.